Pre-Service Special Educators’ Understandings of Relational Competence - Aspelin, Jonas; Östlund, Daniel; Jönsson, Anders (Frontiers in Education, 2021)
Research demonstrates that the teacher-student relationship is essential for students with special educational needs. This article investigates how pre-service special educators (n = 74) perceive teachers’ relational competence, as manifested in their relations with students exhibiting behavioral difficulties. The data comprises educators’ written analyses of teacher-student interactions simulated through digital video, both before and after being provided with explicit criteria on teachers’ relational competence. The findings reveal a change in the educators’ perceptions as they shift from a focus on teaching strategies and the learning environment toward an awareness of teacher-student interaction, and from the teacher’s management of problematic student behavior toward an acknowledgement of the communicative and socio-emotional challenges in contexts involving students with different needs.